Self-Disclosure Here and Now: Combining Retrospective Perceived Assessment With Dynamic Behavioral Measures - Kreiner, Hamutal; Levi-Belz, Yossi (Frontiers in Psychology, 2019)
Most previous research on self-disclosure (SD) focused on its perceived retrospective aspects using self-report questionnaires. Few studies investigated actual SD as reflected in interpersonal interaction. We propose a comprehensive approach that combines new objective and dynamic measures of SD that evaluate situated SD with the traditional measures that evaluate stable SD properties. As SD is essentially verbal, we build on linguistic parameters for assessing actual SD, including acoustic features such as intonation and fluency, and verbal features such as the particular choice of words. Critically, the new measures highlight SD here and now and may reveal transient situational factors that affect it, such as the dynamics of interpersonal interaction. Based on these measures, we propose a 3-dimensional evaluation that can portray different profiles of SD and offer a better prediction of SD behavior in different situations. The theoretical and clinical implications of the proposed approach are discussed.